Monthly availability of total aerial phytomass and in different compartments of a low grassland in the hilly region of La Pampa (Semiárida, 2020)
The work was done in a short grassland in the area of La Pampa hills (Toay department), to determine above ground standing crop, total and of the different compartments. Cuts were done monthly in -an area previously grazed, during a whole year's sampling. Total standing crop of aerial biomass was of 173 gDM/m2 of annual average. The most important valuable species were: Poa ligularis, Piptochaetium napoataense, Bothriochloa springfieldii y Rhynchoaia senna. Living biomasa compartment was at its maximum in summer months, with its greatest contribution in January (131 gDM/m2). The standing dead material increased in autumn reaching the maximum value in June (168 gDM/m2); while the litter had its highest value in September (288 gDM/m2) The grassland studied resulted being biseasonal with a period of greater growing by the end of spring-summer and another minor by the middle of autumn. The passage of the living material to the standing dead compartment was quick. It was also quick the convertion to litter in spring, as a consequence of the intensity of the winds.